Peningkatan Pembelajaran Student-Centered SMAK Santo Yusup Surabaya melalui Penataan Ruang Kelas - Lya Dewi Anggraini; Natalia Christiani; Hebert Adrianto (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
One important factor in improving the quality of learning is the classroom atmosphere, which is formed through the activities carried out in it between the teacher and students with position, posture, and body language, as non-verbal communication, and the use of words, intonation, and pronunciation as verbal communication. Another important factor is the characteristics of the space where the activity takes place (setting). In applying the student-centered approach, which motivates students to learn more actively and not depend on the teacher, the role of a teacher is very important to always be able to improvise, exploit the potential and position, for the success of the teaching-learning process in schools. The purpose of activities in the field of interior science architecture community service at SMAK St. This framework is to strengthen the participation of teachers and students through the setting of learning spaces that support the establishment of communication as desired. The method used is observation of the physical environment and surveys of teachers and students about the communication experience and the convenience of learning on three subjects that are considered difficult, namely Chemistry, Biology, and English. The survey results show that effective verbal and non-verbal communication media between teachers and students and fellow students is triggered by the setting of the space outside the classroom, with more relaxed and enjoyable reasons, such as in a library room. This has a real impact on increasing student motivation in the form of subjects' likes and grades. Other results indicate an increase in teacher awareness that changes in varied learning space settings can support non-verbal communication with students. How to cite:Anggraeni, Lya Dewi. (2020). Peningkatan Pembelajaran Student-Centered SMAK Santo Yusup Surabaya melalui Penataan Ruang Kelas. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1),28-37.DOI: https://doi.org/10.26905/abdimas.v5i1.3100